∫ 1 e ( ( ln x ) 2 + 1 ln x − 1 ) 2 d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done! The property ∫ e x ( f ( x ) + f ′ ( x ) ) . d x = e x f ( x ) + c is very underrated and underutilized for solving integrals.
Nicely done! The property is indeed brilliantly used.
Problem Loading...
Note Loading...
Set Loading...
Put l n x = t limits now become 0 for x = 1 and 1 for x = e
e t = x
e t . d t = d x
by substituting the value value, we get
∫ 0 1 e t ( ( t 2 + 1 ) 2 ( t − 1 ) 2 ) . d t
∫ 0 1 e t ( ( t 2 + 1 ) 2 t 2 − 2 t + 1 ) . d t
∫ 0 1 e t ( t 2 + 1 1 − ( t 2 + 1 ) 2 2 t ) . d t
As per general property ∫ e x ( f ( x ) + f ′ ( x ) ) . d x = e x f ( x ) + c
t 2 + 1 1 i s f ( t ) and ( t 2 + 1 ) 2 − 2 t i s f ′ ( t )
hence the result of integral is t 2 + 1 e t
On applying limits
2 e − 1
=> 0 . 3 5 9 1